THE MELOIDAE (COLEOPTERA) OF WISCONSIN - Marschalek, Daniel A.; Young, Daniel K. (Zootaxa, 2015)
There are recent faunistic surveys of selected insect taxa (e.g. Mutillidae, Scarabaeoidea, and Tenebrionidae) in Wisconsin but a formal investigation of the Meloidae (blister beetles) is lacking. The blister beetle fauna of several states has been published, but this study represents the first in the Midwestern United States. We provide a comprehensive list of all meloid species documented from Wisconsin. Also included are taxonomic keys as well as summaries for each species (species pages) which includes taxonomy, description, and natural history. Specimens were obtained from public and private collections, and field sampling. This survey advances our knowledge of meloids in Wisconsin as well as provides a contribution beyond this geographic area. During this survey, 28 meloid species in seven genera were documented in Wisconsin from 2605 specimens. Of these taxa, 10 species are considered new state records. While Epicauta pensylvanica represented nearly half of the specimens reviewed, and likely inhabits all counties within the state, other species were rarely encountered. This includes 10 species which were represented by seven specimens or fewer in this study. It is unclear if the rarity of these specimens is correlated with the rarity of the species or if it is due to other factors. Regardless, these rarely collected meloids in Wisconsin warrant further attention.